2015
DOI: 10.4141/cjps-2014-290
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and acetolactate synthase inhibitor resistant common ragweed (Ambrosia artemisiifolia L.) in southwestern Ontario

Abstract: . 2015. Glyphosate and acetolactate synthase inhibitor resistant common ragweed (Ambrosia artemisiifolia L.) in southwestern Ontario. Can. J. Plant Sci. 95: 335Á338. Common ragweed (Ambrosia artemisiifolia L.) was found to be resistant to glyphosate in Ontario. Field surveys were conducted from 2011 to 2013 to determine the distribution of glyphosate-resistant (GR) and acetolactate synthase inhibitor resistant common ragweed. GR common ragweed was confirmed in Essex County. All GR populations were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
9
1
Order By: Relevance
“…Finally, seed was collected in areas of previously known waterhemp populations in southwestern Ontario (Costea et al 2005;Vyn et al 2007). The survey methodology used was similar to previous published research for other herbicide-resistant weeds in Ontario (Falk et al 2005;Vink et al 2012;Byker et al 2013;Follings et al 2013;Van Wely et al 2015).…”
Section: Seed Collectionmentioning
confidence: 99%
“…Finally, seed was collected in areas of previously known waterhemp populations in southwestern Ontario (Costea et al 2005;Vyn et al 2007). The survey methodology used was similar to previous published research for other herbicide-resistant weeds in Ontario (Falk et al 2005;Vink et al 2012;Byker et al 2013;Follings et al 2013;Van Wely et al 2015).…”
Section: Seed Collectionmentioning
confidence: 99%
“…As of 2016, glyphosate-resistant (GR) Canada fleabane, giant ragweed, waterhemp, and common ragweed have been confirmed in 30, 6, 3, and 1 counties in Ontario, respectively (Follings et al 2013;Van Wely et al 2015;Budd et al 2017;Schryver et al 2017). With the recent evolution of GR weeds, there has been an increased interest in the use of 2,4-dichlorophenoxyacetic acid (2,4-D) applied late postemergence for the control of GR weeds such as Canada fleabane.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, this field had a soybean-soybean-winter wheat rotation. This population is resistant to ALS (acetolactate synthase) inhibitors and EPSPS (5-enolpyruvyl shikimate-3-phosphate synthase) inhibitors herbicides (Van Wely et al 2014a). Van Wely et al (2014b) reported up to a 28-fold increase in the amount of glyphosate required for a 50% reduction in weed biomass for the biotype at this location compared to the susceptible biotype.…”
Section: Methodsmentioning
confidence: 97%